Reservoir heterogeneity between intra-platform and platform-margin settings in an isolated carbonate platform: a case study from the carboniferous, Pre-Caspian Basin - Zheng, Tianyu; Wen, Jiajun; Zhao, Lun; Zeng, Xing; Wang, Shuqin; Chen, Yefei; Hou, Jue (Frontiers in Earth Science, 2026)
IntroductionThe Carboniferous isolated platform carbonate reservoirs in the Pre-Caspian Q6 Basin exhibit pronounced heterogeneity, which significantly constrains the effective prioritization and optimization of exploration targets. This study aims to elucidate the differential characteristics and genetic mechanisms of intra-platform and platform-margin reservoirs within the Carboniferous Unit 1 isolated carbonate platform in the southern Pre-Caspian Basin.MethodsBy integrating core and thin-section observations with porosity, permeability, mercury injection capillary pressure (MICP) data, and production performance analysis, we systematically compared the reservoir properties of the two settings.ResultsThe results indicate that reservoir differentiation is primarily controlled by differential karstification within a unified depositional framework. Although both intra-platform and platform-margin settings exhibit comparable lithologies (mainly grainstones and packstones), their pore structures differ significantly. Intra-platform reservoirs are dominated by matrix porosity (e.g., selective dissolution pores) and show favorable porosity-permeability relationships. In contrast, platform-margin reservoirs develop heterogeneous fracture-vug systems, resulting in poor porosity-permeability correlations, while conventional core analysis systematically underestimates their actual flow capacity. Distinct karstification processes govern this spatial heterogeneity: facies-controlled penecontemporaneous dissolution shapes matrix porosity in intra-platform areas, whereas superimposed multi-phase coastal karstification creates complex fracture-vug networks along the platform margin. A differential pore evolution model is established to illustrate these mechanisms.Discussion and ConclusionThese findings highlight the critical role of differential karstification in the diagenetic pathways of carbonate reservoirs. They not only elucidate the genetic mechanisms behind reservoir quality differences but also offer practical implications for reservoir evaluation and provide a robust theoretical foundation for predicting high-quality carbonate reservoirs in the study area and analogous geological settings.